PEMODELAN DINAMIK DAN VALIDASI MODEL DARI SISTEM KENDALI TANGKI GANDA - Zainal Abidin; Priyono Sutikno; Is Maryanto; Ilham B Santoso (Mesin, 1997)
This paper describes dynamic modeling and model validation of a couple-tank control system which consist of a couple-tank, two motor-and-pumps, two electric-motor drivers, and two water-level sensors. Initially, dynamic modeling of the couple-tank was derived analytically. This derivation produced several parameters whose values were unknown. Experiments were then performed in order to obtain the values of those parameters. In addition to the couple-tank, other components were also modeled statically. Once all components of the couple-tank controlled system have been modeled, model validation of the whole system can then be performed.